Implementasi Good Governance dalam Kinerja Pegawai Pada Kantor Kecamatan Cimahi Tengah - Lena Oktaviani; Kurhayadi Kurhayadi; Rezky Afiahtul Barokah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The government has a role in the implementation of good governance that in decision making is very important, good governance practices are able to be implemented, so that people can participate in Good Governance in employee performance at the Central Cimahi Sub-district Office. This research uses qualitative research method by the way of illustrating the synergistic problems when the research is done. Data collection techniques performed with observations, interviews and documents. The instrument used in this research is observation sheet, interview sheet, and structured documentation made by the researcher. The results showed that the implementation of good governance in employee performance at the Central Cimahi Sub-district office has been in accordance with the goods of good governance policies and this is seen from how employee performance and community satisfaction in providing services.